NEW GEOPHYSICAL INVESTIGATIONS RESULTS AT THE AREA OF LARGE ZINC ORES DEPOSIT «SHAYMERDEN» (REPUBLIK KAZAKHSTAN) - Levashov, S.; Yakimchuk, N.; Korchagin, I.; Yakubovskiy, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The results of the technology approbation of the satellite data processing and interpretation for the "direct" prospecting the ore minerals are analyzed. They witness that technology allows to find and map operatively the anomalous zones of "zone of ore mineralization" type, which are conditioned by the deposits of gold, uranium, zinc, iron, and etc. The satellite data processing results are analyzed in region of the big zinc deposit location in Republic of Kazakhstan. It is shown that the ore objects of small sizes (100–300 m) can be discovered and mapped when the vast scale (1:10000 and more large) and resolution satellite data processing and interpreting.